Apparent Inadequate Fixation Due to Improper Radiographic Angulation - Silva de Oliveira, Julio Cesar [UNESP]; Alonso da Luz, Bruno Henrique [UNESP]; Pereira Santos, Deborah Laurindo [UNESP]; Monnazzi, Marcelo Silva [UNESP] (Springer, 2018)
Computed tomography is shown as an alternative important aid for diagnosis and postoperative evaluation in the maxillofacial region.
Keywords: Zygomatic fracture; Radiograph; Fixation; Maxillofacial; CT scan